Functional characterization of Synechococcus amylosucrase and fructokinase encoding genes discovers two novel actors on the stage of cyanobacterial sucrose metabolism - Perez Cenci, Macarena (2014)
Plants and most cyanobacteria metabolize sucrose (Suc) with a similar set of enzymes. In Synechococcus sp. PCC 7002, a marine cyanobacterium strain, genes involved in Suc synthesis (spsA and sppA) have been characterized; however, its breakdown was still unknown. Indeed, neither invertase nor sucrose synthase genes, usually found in plants and cyanobacteria, were found in that Synechococcus genome. In the present study, we functionally characterized the amsA gene that codes for an amylosucrase (AMS), a glycoside-hydrolase family 13 enzyme described in bacteria, which may catabolyze Suc in Synechococcus. Additionally, we identified and characterized the frkA gene that codes for a fructokinase (FRK), enzyme that yields fructose-6P, one of the substrates for Suc synthesis. Interestingly, we demonstrate that spsA, sppA, frkA and amsA are grouped in a transcriptional unit that were named Suc cluster, whose expression is increased in response to a salt treatment. This is the first report on the characterization of an AMS and FRK in an oxygenic photosynthetic microorganism, which could be associated with Suc metabolism.